2005
DOI: 10.1021/jp045928i
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Structure and CO Oxidation Activity of Ceria-Supported Gold Catalysts

Abstract: Gold catalysts supported on cerium oxide were prepared by solvated metal atom dispersion (SMAD), by deposition-precipitation (DP), and by coprecipitation (CP) methods and were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR), and X-ray photoelectron spectroscopy (XPS). The catalytic activity was tested in the CO oxidation reaction. The structural and surface analyses evidenced the presence of a modified ceria phase in the case of the DP sample and the presence of pure ceria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
182
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(193 citation statements)
references
References 48 publications
9
182
0
2
Order By: Relevance
“…/Ce 4? by Au 3? [20,[37][38][39][40]. Recently, EXAFS structure analysis showed that the isolated Au cations in leached Au/CeO 2 are surrounded by oxygen and cerium, respectively, in the first and second coordination shell in agreement with Au substitution for Ce [11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…/Ce 4? by Au 3? [20,[37][38][39][40]. Recently, EXAFS structure analysis showed that the isolated Au cations in leached Au/CeO 2 are surrounded by oxygen and cerium, respectively, in the first and second coordination shell in agreement with Au substitution for Ce [11].…”
Section: Introductionmentioning
confidence: 91%
“…In line with the importance of the interactions between gold and the support, it has been found that nanoscale forms of ceria contribute to the high activity of small gold particles [18][19][20][21][22][23][24]. Several authors [25][26][27][28] have used nanostructured ceria that expose certain planes to investigate the influence of the nature of the ceria surface on the nature and activity of gold species.…”
Section: Introductionmentioning
confidence: 99%
“…6 shows the H 2 -TPR profiles of CeO 2 and Ag/CeO 2 nanomaterials. All CeO 2 samples exhibited a broad reduction peak at 400-600°C, which was the hydrogen consumed peak of surface oxygen [18,25]. The more intense low-temperature reduction peaks of the CeO 2 nanorods and nanocubes indicated that a higher amount of hydrogen was consumed, i.e.…”
Section: Characterization and Effects Of Shape Crystalline Phase Andmentioning
confidence: 97%
“…Due to the high oxygen transport and storage capacities of ceria (CeO 2 ), notable surface oxygen species form on CeO 2 nanomaterials [17] widely employed in heterogeneous catalysis [18][19][20]. Ceria is an interesting oxide because oxygen vacancy defects can be rapidly formed, thus O vacancies and ROS in CeO 2 are naturally anticipated in catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…As was established, during the reaction in the dry condition the oxidized gold phases (Au 2 O 3 in Au/Fe 2 O 3 , Au(OH) 3 and Au 2 O 3 in Au/Al 2 O 3 ), which coexisted in the as-prepared catalysts along with Au 0 , were reduced almost completely to metallic Au, however after the reaction in the wet condition about 40% of the oxidic gold remained. The gradual reduction of Au III species to metallic gold in an Au/Fe 2 O 3 catalyst was also observed in work [4], whereas in an Au/CeO 2 catalyst the Au III ions were reduced under CO oxidation reaction conditions to Au  species [5]. The data on the chemical and electronic state of gold nanoparticles in different catalysts used in the CO oxidation as determined by the Au 4f binding energy are rather contradictory, although they clearly indicate that formation and modification of the particles' electronic state strongly depend on the nature of support.…”
Section: Introductionmentioning
confidence: 53%